Drought Terroirs. Debating anthropological territorialities in the study of climate change and environmental disasters - Blanes, Ruy Llera; Cardoso, Carolina Valente; Bahu, Helder Alicerces; Fortuna, Cláudio (Kritisk Etnografi: Swedish Journal of Anthropology, 2022)
The term ‘terroir’ is traditionally used in wine making; in this article, we perform an analytical intervention on the concept of ‘terroir,’ as a potentially useful category to think through issues of territoriality in the framework of environmental disaster from an anthropological perspective. Incorporating ethnographic fieldwork on the extreme drought that has been unfolding in Southwestern Angola since 2009, we explore the analytical potential of ‘drought terroirs’ to untap the complexities and scales of environmental disaster, and at the same time debate the problem of territoriality as an ethnographic problem. We argue that an ethnographic transposition of ‘terroir’ into ‘drought terroir’ can help us grasp further complexities and nuances of territoriality in terms of scale, agency, and temporality in the face of current debates on global climate change.